PEMANFAATAN MEDIA VIDEO ANIMASI UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS V A SDN MENANGGAL - Auliyah, Fenti Rizqi; Juniarso, Triman (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2021)
The Human Circulatory System for grade VA students at SDN Menanggal 601 Surabaya. This study uses Classroom Action Research using animated video learning media. The data source of this research is that there are 40 students of class VA SDN Menanggal 601 Surabaya. The data collection techniques used were observation, tests and documentation. Furthermore, the first data analysis technique uses descriptive qualitative to explain the process of using animative video learning media. The second data analysis technique uses descriptive quantitative to show the learning outcomes of students. Based on the research, it shows that the use of animated video media can improve student learning outcomes in the VA class of SDN Menanggal 601 Surabaya. It can be seen from before being given the action only 13 students or 32.5% reached the KKM. After being given the action in cycle II as many as 39 students or 97